Search for production of WW/WZ resonances decaying to a lepton, neutrino and jets in pp collisions at √s = 8 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Hanke, Paul; Jongmanns, Jan; Kluge, Eike-Erik; Kugel, Andreas; Lang, Valerie; et al. (The European physical journal. C, Particles and fields, 2015)
A search is presented for narrow diboson resonances decaying to WW or WZ in the final state where one W boson decays leptonically (to an electron or a muon plus a neutrino) and the other W/Z boson decays hadronically. The analysis is performed using an integrated luminosity of 20.3 fb−1 of pp collisions at s√=8 TeV collected by the ATLAS detector at the large hadron collider. No evidence for resonant diboson production is observed, and resonance masses below 700 and 1490 GeV are excluded at 95 % confidence level for the spin-2 Randall–Sundrum bulk graviton G∗ with coupling constant of 1.0 and the extended gauge model W′ boson respectively.